2015
DOI: 10.1002/alr.21486
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic proteolytic responses in chronic rhinosinusitis with nasal polyposis and asthma

Abstract: Our findings suggest shared pathomechanisms behind asthma and CRSwNP. Contrasting local vs systemic results reflect a different ability of healthy mucosa to react to exogenous stimuli, possibly indicating a protective function of MMP-9 and possibly also MMP-8 in the airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
(83 reference statements)
0
12
0
1
Order By: Relevance
“…Neutrophil elastase plays an important role in the development of airway inflammation and hyperresponsiveness, which are key factors in the pathophysiology of asthma [84]. Compared to healthy controls, patients with bronchial asthma have a higher activity of neutrophil elastase [85,86]. In asthmatics, VIGNOLA et al [87] showed that neutrophil elastase activity is negatively correlated with FEV1.…”
Section: Risk Of Asthma In the Mz Populationmentioning
confidence: 99%
“…Neutrophil elastase plays an important role in the development of airway inflammation and hyperresponsiveness, which are key factors in the pathophysiology of asthma [84]. Compared to healthy controls, patients with bronchial asthma have a higher activity of neutrophil elastase [85,86]. In asthmatics, VIGNOLA et al [87] showed that neutrophil elastase activity is negatively correlated with FEV1.…”
Section: Risk Of Asthma In the Mz Populationmentioning
confidence: 99%
“…MMPs and their tissue inhibitors (TIMPs) are considered to play important roles in nasal polyp formation [36]. MMP-9, secreted by epithelial cells, EOS, mast cells and activated neutrophils, plays a critical role in tissue remodeling in CRS through decomposing the components of ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Higher levels of MMP-9 and low levels of TIMP-1 were observed in patients with CRSwNP. Meanwhile, MMPs were also found to participate in regulating inflammatory cells infiltration and microvascular permeability in allergic disorders including AR and asthma [36, 38]. Increased expression of MMP-9 and ratio of MMP-9/TIMP-1 were observed in AR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, local expression and activity of individual MMPs may vary in different airway compartments, thus adding complexity to the network of allergic inflammatory response. [61,78,122] Accordingly, the distribution of MMP-2, MMP-9 and MMP-12 in bronchial wall was shown to differ between large and small airways. Moreover, it varied between healthy controls and patients with asthma, and further changed depending on severity of disease.…”
Section: Discussionmentioning
confidence: 99%